President's Message (Academy of Management Journal, 1970)
The article presents a note from the President of the Academy of Management. He focuses on events that have occurred since the association's conception. It is suggested that the end of the Cold War prompted a major shift in industrial management. Government financing of industrial research is discussed in relation to the national science policy of the U.S.